Zn/MeOH-Mediated Practical and Easy Detritylation of Protected 1-Trityltetrazoles - Behloul, Cherif; Bouchelouche, Kenza; Hadji, Yasmine; Benseghir, Saadia; Guijarro, David; Nájera, Carmen; Yus, Miguel (Synthesis, 2016)
A practical and low-cost method for the detritylation of 1-titryltetrazoles using zinc and methanol is described. This procedure is versatile and efficient in the deprotection of several protected tetrazoles bearing aliphatic, aromatic, and heteroaromatic substituents, as well as some functional groups, without decomposition of the tetrazole ring.
Keywords: tetrazoles; zinc/methanol; detritylation; reductive cleavage